The Effect of Temperature Variations in the Pressing Process on Glossing Defects Bigborn 2-Tuck Pants Style 3651 Trousers in the Finishing Department of PT. X - Afriani Kusumadewi; Feny Nurherawati; Filly Pravitasari (Sainteks: Jurnal Sain dan Teknik, 2023)
Abstract: The pressing process is a process of applying heat and pressure at a predetermined time. Temperature, time and pressure in the pressing process in the finishing department play an important role in the quality of the results of pressing garment products at PT X. Various types of main materials used in the garment production process at PT X require different conditions of temperature, time and pressing pressure, so it is necessary to know the appropriate pressing conditions for each type of material. If these three elements are not appropriate, it can give rise to several categories of defects, one of which is often experienced by PT X, namely glossing/shiny defects. The method that used in this research was carried out by experimenting with variations in pressing temperature where the time and pressure variables used were fixed. The temperature variations used in this research include 600C, 700C, 800C, 900C and 1000C.. This research aims to determine the optimum temperature that used in the pressing process in making Bigborn 2-Tuck Pants Style 3651 trousers with the main material composition being 65% Polyester and 35% Katun. The pressing results are then tested for the tensile strength of the fabric towards the warp and towards the weft of the fabric. Based on the experiments carried out, it shows that for temperature variations of 600C and 700C there are poor press defects. At varying temperatures of 800C and 900C, there are no glossing defects. At 1000C it has glossing/shiny defect. Next, to obtain the most optimum temperature conditions, the experiment continued with testing the tensile strength of the fabric. Based on the fabric tensile strength test data, an optimum temperature condition was obtained in the process of pressing Bigborn 2-Tuck Pants Style 3651 trousers, namely at a temperature of 800C. The tensile strength results obtained at a temperature of 800C were 55 kg for the tensile strength of the fabric in the warp direction and the tensile strength of the fabric in the weft direction was 45.5 kg. Keywords: temperature, pressing, glossing